Na+‐taurocholate cotransporting polypeptide inhibition has hepatoprotective effects in cholestasis in mice. Issue 3 (27th April 2018) - Slijepcevic, Davor; Roscam Abbing, Reinout L.P.; Fuchs, Claudia D.; Haazen, Lizette C.M.; Beuers, Ulrich; Trauner, Michael; Oude Elferink, Ronald P.J.; van de Graaf, Stan F.J.
Abstract : Accumulation of bile salts (BSs) during cholestasis leads to hepatic and biliary injury, driving inflammatory and fibrotic processes. The Na + ‐Taurocholate Cotransporting Polypeptide (NTCP) is the major hepatic uptake transporter of BSs, and can be specifically inhibited by myrcludex B. We hypothesized that inhibition of NTCP dampens cholestatic liver injury. Acute cholestasis was induced in mice by a 3.5‐diethoxycarbonyl‐1.4‐dihydrocollidine (DDC) diet or by bile duct ligation (BDL). Chronic cholestasis was investigated in Atp8b1 ‐G308V and Abcb4/ Mdr2 deficient mice. Mice were injected daily with myrcludex B or vehicle. Myrcludex B reduced plasma alkaline phosphatase (ALP) levels in DDC‐fed, Atp8b1 ‐G308V and BDL mice by 39%, 27% and 48% respectively. Expression of genes involved in fibrosis, proliferation and inflammation was reduced by myrcludex B treatment in DDC‐fed and Atp8b1 ‐G308V mice. NTCP‐inhibition increased plasma BS levels from 604±277 to 1746±719 μm in DDC‐fed mice, 432±280 to 762±288 μm in Atp8b1 ‐G308V mice and from 522±130 to 3625±378 μm in BDL mice. NTCP‐inhibition strongly aggravated weight loss in BDL mice, but not in other cholestatic models studied. NTCP‐inhibition reduced biliary BS output in DDC‐fed and Atp8b1 ‐G308V mice by ∼50% while phospholipid (PL) output was maintained, resulting in a higher PL/BS ratio. Conversely, liver injury in Abcb4 deficient mice, lacking biliary phospholipid output, was aggravated after myrcludex B treatment. Conclusion : NTCP‐inhibition by myrcludex B has hepatoprotective effects, by reducing BS load in hepatocytes and increasing the biliary PL/BS ratio. High micromolar plasma BS levels after NTCP‐inhibition were well tolerated. NTCP‐inhibition may be beneficial in selected forms of cholestasis. (Hepatology 2018).